Outcome Melatonin Supplementation on Insulin Resistance in a Sample of Iraqi Acromegalic Patients with Sleep Apnea - Hamid, Yusr abdulkarim; kadhim, Kadhim Ali; Rahmah, Abbas Mahdi (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2019)
Sleep apnea, a common respiratory complication of acromegaly is accountable for 25% of deaths in acromegalic patients. It contributes to increasing cardiovascular diseases and raising mortality rate in acromegalic patients and still persists after control of acromegaly. Raised insulin resistance that was noticed in some acromegalic patients are believed to be caused by acromegaly itself, weight gain, octreotide therapy or the deleterious effect of sleep apnea itself. It was found that both acromegaly and sleep apnea share a disordered melatonin secretion. Numerous clinical and experimental studies have shown a promising role of melatonin as an antidiabetic agent. Nevertheless, no other study had examined the effect of melatonin supplementation on insulin resistance level in acromegalic patients receiving their standard treatment and experiencing some sleep difficulties. The study was designed to scrutinize the effect of melatonin supplementation on insulin resistance in controlled acromegalic patients who had been receiving their standard treatment. It was a prospective randomised controlled open labelled study included 27 Iraqi acromegalic patients. Their age ranged (29-57).The patients were receiving their usual octreotide monthly dose determined by the physician to control their disease and they had moderate to severe sleep apnea (Epworth sleepiness scale and STOP-BANG score were used to include them in the study ,they were enrolled if the summation of their ESS points ≥10 or of their STOP-BANG points ≥3).The patients were divided into two groups, group 1 included 15 patients taking their usual octreotide dose once monthly plus 5 mg of melatonin at night, group 2 included 12 patients taking their usual octreotide dose only. Blood samples were taken at fasting state at baseline and after 2 months to estimate serum growth hormone (GH), insulin like growth factor-1 (IGF-1), insulin and blood glucose. The homeostatic model assessment for insulin resistance (HOMA) result was calculated for each subject. At the end of the study period, melatonin treated group showed no significant change in GH, IGF-1, a highly significant decrease in glucose level (p<0.001), a highly significant decrease in insulin (p<0.001) and a highly significant decrease in HOMA score (p<0.001).Standard treatment group showed no significant difference in GH, IGF-1, insulin level and HOMA score at the end of the two months study period and a highly significant increase in glucose level. In conclusion, our study has confirmed the existing evidence of that melatonin supplementation improves glucose homeostasis and offers promising tool for future studies in acromegalic patients and larger trials.